KERANGKA METODOLOGI PENALARAN HUKUM - Amir, Rahma (Al AHKAM: Jurnal Kajian Ilmu Hukum dan Syariah, 2015)
Type methodic law find or method even implement sentence in islamic law (istinbathal hukm) and law implement (tathbiq al hukm), in real islamic law not far in contrast to findmethod sentences and law implement that utilized by common law practitioner. Such too withmethod that diberlakukan in a state terminologicals islamic law already dikemukan by JurisIslam (fuqaha), as understanding as law which exists deep text sentence to be assessed byhermeneutikas method and also of its language facet the so called Ushul Fiqh. In knowledgeUshul Fiqh formulated by method understands islamic law and understand law theorems, withthat theorem law what do come into the world according to common sense (a. reasionableassumption) .